How does resilience affect the performance of nurses in psychiatric hospital? - Hidayati, Fitria; Saimi, Saimi; Sastrawan, Sastrawan (Journal of Midwifery and Nursing, 2024)
The complex challenges in these environments demand extraordinary skill and resilience from nurses. This research aims to explore the influence of resilience on the performance of nurses at Mutiara Sukma Psychiatric hospital. The research method used a quantitative approach with a sample size of 110 nurses. Sampling was carried out using the Slovin formula and quota sampling technique. Data on nurses' resilience and performance were collected through questionnaires whose validity and reliability were tested. Data analysis involves inferential statistical techniques, such as independent t tests and simple linear regression. The independent t test was used to compare the average performance between low and high resilience groups, while simple linear regression was used to assess the linear relationship between resilience (independent variable) and performance (dependent variable). Data was processed using the SPSS program. The results of data analysis show that nurses with a high level of resilience tend to have better performance. Independent t tests revealed significant differences in performance between the low and high resilience groups. In addition, simple linear regression shows that resilience has a positive effect on nurse performance. The practical implications of this research provide a basis for developing training and support programs to increase nurse resilience, with the aim of improving service quality. This research provides an in-depth understanding of individual psychological relationships with a direct impact on mental health services. Despite these limitations, these findings have significant relevance for human resource management in hospitals and can serve as a basis for future research.